2016
DOI: 10.1126/sciadv.1600014
|View full text |Cite
|
Sign up to set email alerts
|

Copper-induced structural conversion templates prion protein oligomerization and neurotoxicity

Abstract: Copper induces prion protein misfolding, aggregation, and neurotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 78 publications
0
40
0
Order By: Relevance
“…As a consequence, structural sub-populations—including intermediates in a heterogeneous ensemble—can be distinguished and characterized directly, and the rare and/or transient states that are commonly associated with misfolding can be identified and probed 39 42 . Single-molecule methods have been used to study prion proteins 39 , 43 46 and other proteins with prion-like properties such as α-synuclein 40 , 47 50 and Aβ 50 , 51 , as well as to study disulfide-bond isomerization in SOD1 52 , but they have not yet been applied to study misfolding in SOD1.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, structural sub-populations—including intermediates in a heterogeneous ensemble—can be distinguished and characterized directly, and the rare and/or transient states that are commonly associated with misfolding can be identified and probed 39 42 . Single-molecule methods have been used to study prion proteins 39 , 43 46 and other proteins with prion-like properties such as α-synuclein 40 , 47 50 and Aβ 50 , 51 , as well as to study disulfide-bond isomerization in SOD1 52 , but they have not yet been applied to study misfolding in SOD1.…”
Section: Introductionmentioning
confidence: 99%
“…The present case may well be the first report of Wilson's and Creutzfeldt-Jakob diseases co-morbidity, suggesting a possible association of copper metabolism with the pathogenesis of CJD. Several recent studies investigate the relationship of copper and prion protein and its role in the pathogenesis of the CJD which remains unclear [7][8][9]. This case sparks a new clinical interest in pursuing further research in this direction.…”
Section: Discussionmentioning
confidence: 98%
“…Examples of the TSEs include mad cow disease, chronic wasting disease in deer and elk, scrapie in goats and sheep, and kuru and Creutzfeldt-Jakob disease (CJD) in humans. Sporadic and inherited prion diseases fall into the same class as Alzheimer's and Parkinson's disease, insofar that they are all associated with the accumulation of endogenous protein aggregates [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This effect, seen with histidine-containing wt OR units, has been ascribed to a conformational aspect of metal-binding to the OR region, where insertions impede the ability to transition from a configuration denoted "component 3" to a multivalent configuration, "component 1" [ 54 ]. Overall, an extensive literature contains complex, and sometimes contrasting, findings [ 55 58 ]; taken together one may surmise that the OR region has pleiotropic effects, i . e .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, and bearing in mind that mature wt PrP C is normally considered to exist a monomer, Yen et al . reported that copper-induced structural conversion of wt PrP C predisposes it for oligomerization that is associated with toxicity [ 58 ]. Thus, we arrive at opposite predictions that in the presence of copper, the OR region of the PrP(TetraH>G) allele is now susceptible to misfolding under low Cu(II) occupancy or is prevented from Cu-dependent oligomerization.…”
Section: Discussionmentioning
confidence: 99%